Lexicalisation of crop names in Bena, Hehe, and Sangu societies of Tanzania - Adriano Utenga; Amani Lusekelo (Cogent Arts & Humanities)
This paper examines the names of crops in the Bantu languages Bena, Hehe, and Sangu. This was sparked by the realisation that certain crops are native to Africa while others were introduced to inland Bantu languages through interactions with coastal communities. Coastal communities acquired these crop names from Asian and European languages before presenting them to the interior regions. The theory of lexicalisation guided this study to account for the nativisation and coinage of crop names. Data were collected through fieldwork in Iringa, Njombe and Mbeya regions. Five elderly speakers of each language were acquired through purposive and snowball sampling techniques. The study found three layers of crop names among Bena, Hehe, and Sangu: one crop with a single name among the three languages, one crop with different names in the three languages, and one crop with multiple names within a single language. Additionally, the study found that the three languages lexicalise crop names by coining expressions and borrowing from Kiswahili. Coinage of expressions was achieved through semantic extension and adjustments of previously existing words or crop names. The study extends the theory of lexicalisation by examining how borrowing, semantic extension, and cultural integration influence crop naming in Bantu languages.